Reconstruction of Knowledge on Women's Body and Beauty During the Late Ming Period: Women's Knowledge in Fragrant Toilette to Embellish Beauty - Guo, Jingya. (2018)
Abstract: The aim of this thesis is to examine the knowledge on women's body and beauty in the Fragrant Toilette to Embellish Beauty (Xiang Lian Run Se), which is a daily-use encyclopedia compiled and printed by a Hangzhou book merchant-scholar Hu Wenhuan during the late Ming period (1368-1644) . It stands out as a special encyclopedia because of its comprehensiveness and concerns about women's beauty maintenance and body cultivation. By comparing it with daily-use encyclopedias (Riyongleishu) and medical prescription book (Fangshu), I will restore the process of how Hu Wenhuan distributed and integrated other textual sources into the Fragrant Toilette to Embellish Beauty. This paper mainly argues that the Fragrant Toilette to Embellish Beauty targeted women as its main audiences and reflected the book compiler's inclination of gendering knowledge due to the commercial culture of the late Ming society.; Thesis (M.A.)--Tufts University, 2018.; Submitted to the Dept. of History.; Advisor: Man Xu.; Committee: Elizabeth Remick, and Diane O'Donoghue.; Keywords: History, Asian history, and Asian studies.